Global Trends and Local Gaps: A Bibliometric Analysis and Case Series of Neonatal Conjunctivitis in Southeast Asia - Nurhidayat, Bimanda Rizki; Hibatulloh, Muhammad Farhan; Irwanda, Thalita Permata P.; Farhah, Anitya Izdihar; Devi, Rossi Silvia (Universitas Airlangga, 2026)
Introduction: Neonatal conjunctivitis, or ophthalmia neonatorum, is a preventable disease but is frequently neglected, especially in developing regions such as Southeast Asia, due to limited data availability and public awareness. This study aims to investigate global research trends in neonatal conjunctivitis through bibliometric mapping while concurrently presenting clinical patterns through a localized case series from Indonesia. Case Presentation: A comprehensive bibliometric analysis was conducted using RStudio on 468 articles from the Web of Science database. Simultaneously, two clinically validated cases of neonatal conjunctivitis were documented to exemplify local diagnostic and management challenges. The bibliometric analysis indicated a substantial escalation in global research activity on neonatal conjunctivitis over the preceding two decades; however, it also revealed a pronounced underrepresentation from low- and middle-income nations. The case series provided insight into typical presentations of Neisseria gonorrhoeae (N. gonorrhoeae)-associated and empirically treated conjunctivitis, underscoring issues such as delayed diagnosis, inadequate prior treatment, and the critical significance of appropriate antibiotic administration and follow-up care. Conclusion: The uneven distribution of research efforts in high-income nations, coupled with enduring clinical deficiencies in Southeast Asia, underscores the urgent need to develop regionally tailored public health strategies. Enhanced antenatal screening, education for healthcare providers, and the establishment of standardized neonatal prophylactic protocols are essential to mitigate the incidence and long-term repercussions of neonatal conjunctivitis.